ENGINEERING EDUCATION IN THE USA - Tat’yana B. Mednikova; Vasiliy S. Senashenko (Высшее образование в России)
The article examines education of engineering workforce as one of the priority areas for the US education system development, analyzes the structure of undergraduate engineering programs, discusses the quality of engineering education, as well as the issue of meeting the requirements of the labor market and other problems of the USeducation system, related to education of highly2qualified specialists in engineering.